2006
DOI: 10.1039/b606975d
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of microbiologically polluted aquaculture waters by a novel photochemical technique of potentially low environmental impact

Abstract: The applicability of a novel procedure for the disinfection of microbiologically polluted waters from fish-farming ponds, based on the combined action of visible light (including sunlight) and porphyrin-type photosensitising agents, has been investigated using (a) cell cultures of a Gram-positive bacterium (meticillin-resistant Staphylococcus aureus), a Gram-negative bacterium (Escherichia coli) and a fungal pathogen (Saprolegnia spp.); (b) pilot aquaculture plants involving either spontaneously or artificiall… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
52
0
1

Year Published

2011
2011
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 59 publications
(53 citation statements)
references
References 31 publications
0
52
0
1
Order By: Relevance
“…Experiments with Saprolegnia (≈10 8 zoospores mL −1 ), indicated that Tri-Py + -C 14 -Py + -Me caused a decrease of the survival of the fungal cells by about 6 logs, after phototreatment with 10 M [81]. The preventive protocol determined a reduction of the infected percentage to 10% and 13%, respectively, after one week, with irradiated Tetra-Py + -Me and unirradiated Tri-Py + -C 14 -Py + -Me, respectively.…”
Section: Water Disinfectionmentioning
confidence: 99%
See 3 more Smart Citations
“…Experiments with Saprolegnia (≈10 8 zoospores mL −1 ), indicated that Tri-Py + -C 14 -Py + -Me caused a decrease of the survival of the fungal cells by about 6 logs, after phototreatment with 10 M [81]. The preventive protocol determined a reduction of the infected percentage to 10% and 13%, respectively, after one week, with irradiated Tetra-Py + -Me and unirradiated Tri-Py + -C 14 -Py + -Me, respectively.…”
Section: Water Disinfectionmentioning
confidence: 99%
“…No [47] No [50,52,69] On filter paper [82] On cotton fabric [86,108] On polysilsesquioxane plastic films [61] On cotton fabric [87] On azide-modified cellulose nanocrystals [43,75] On chloroacetyl cellulose ester chlorides [78] On cellulose laurate esters plastic films [79] No [71] No [93] No [49,71,93,110] and Tri-Py + -Me-PF on silica coated Fe3O4 nanoparticles [70] and also on CoFe2O4 nanoparticles [111] No [81] No [105] No [36,37,71,74,81,105]; Tetra-Py + -Me was entrapped into microporous silica gels [88] and into three alkylene-bridged polysilsesquioxanes [89] On optically transparent indium tin oxide electrodes [63] On chitosan membranes [72] Pd(II) TetraTPPCO2H On a polyurethane matrix [83] No [105] In hydrophilic polycaprolactone and polyurethane (TecophilicH) nanofibers [60]; on electrospun polymeric nanofiber materials polyurethane Larithane TM , polystyrene, polycaprolactone, and polyamide 6 [76]; into three alkylene-bridged polysilsesquioxanes [89]; and in a silica-gel supported antimony porphyrin complex SbTPP [97,98] No [44,…”
Section: Porphyrinmentioning
confidence: 99%
See 2 more Smart Citations
“…Approved initially for the treatment of a small number of selected tumors (1), it has expanded to encompass a wide range of applications in dermatology (2,3), ophthalmology (4,5), dentistry (6,7), cardiology (8,9), cosmetics (10,11), blood purification (12), and water disinfection (13,14).…”
Section: Photodynamic Therapy (Pdt)mentioning
confidence: 99%